2022
DOI: 10.1002/lno.12234
|View full text |Cite
|
Sign up to set email alerts
|

Coral reef erosion: In situ measurement on different dead coral substrates on a Caribbean reef

Abstract: The version presented here may differ from the published version. If citing, you are advised to consult the published version for pagination, volume/issue and date of publication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…4). This is consistent with other observations of erosion following coral mortality (60)(61)(62)(63). Because predictions were based on existing relationships between live coral and rugosity in the Caribbean, these modeled reductions in rugosity following SCTLD are likely underestimates, as bioerosion will continue to lower rugosity, even without additional coral death.…”
Section: Resultssupporting
confidence: 87%
“…4). This is consistent with other observations of erosion following coral mortality (60)(61)(62)(63). Because predictions were based on existing relationships between live coral and rugosity in the Caribbean, these modeled reductions in rugosity following SCTLD are likely underestimates, as bioerosion will continue to lower rugosity, even without additional coral death.…”
Section: Resultssupporting
confidence: 87%
“…Caution is needed, however, when comparing parrotfish erosion estimates derived from small experimental blocks made from one coral type ( Porites sp.) with those on natural reef surfaces, as likely differences in skeletal density, surface morphologies, and the age and composition of the organisms on experimental blocks vs. natural surfaces may result in different rates of grazing (Taylor et al 2020; Molina‐Hernández et al 2022). Nonetheless, the high rates of external erosion on blocks, combined with high estimates of parrotfish erosion and the positive correlation between these two estimates among sites ( r 2 = 0.49), supports the theory that grazing parrotfish were the dominant source of erosion at Ningaloo.…”
Section: Discussionmentioning
confidence: 99%
“…Molina‐Hernández et al. (2022) investigated the impact of external bioerosion on recently deceased coral heads and found greater loss of substrate height on corals with lower density; the loss being attributed mostly to grazing by parrotfish. Conversely, some studies focusing on internal macroboring as a whole (e.g., by bivalves, worms, sponges) suggested that bioerosional damage to reef corals was positively correlated with skeletal density (Cosain‐Díaz et al., 2021; Hernández‐Ballesteros et al., 2013; Highsmith, 1981; Highsmith et al., 1983; Hutchings, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…quire the removal of a greater mass of material compared to more porous substrates Molina-Hernández et al (2022). investigated the impact of external bioerosion on recently deceased coral heads and found greater loss of substrate height on corals with lower density; the loss being attributed mostly to grazing by parrotfish.…”
mentioning
confidence: 99%